Lesson study for learning community: A way of collegial participation of teachers and lecturers - Dwi Setyawan; Tutut Indria Permana; Roimil Latifa (JURNAL BIOEDUKATIKA, 2019)
The Lesson Study for Learning Community (LSLC) has become promising for improving school progress. However, there has not been much assistance in the community of teacher learning and collaboration that should lead to new approaches to increase classroom learning quality. This study aimed to explain how the process of assessing and the implementation LSLC at SMA Negeri 4 Malang. This qualitative descriptive study uses teachers and lecturers as research subjects with an unspecified amount in their participation. The data was obtained by using a monitoring checklist, interview, and documentation of the implementation lesson study. The results showed that the application of LSLC was running well, but at the 'Do' phase, there were still observers who worked not following their assignment procedures, and the involvement of teachers in LSLC activities even less. Therefore, it is suggested to implement LSLC which improve collegial participation of teachers and lecturers.